Impact of a palliative care initiative on end-of-life care in the general wards: A before-and-after study. (January 2014) - Tan, Adeline; Seah, Angeline; Chua, Gerald; Lim, Tow Keang; Phua, Jason
Background: Data on deaths in the general wards of our hospital in 2007 revealed infrequent discussions on end-of-life care and excessive burdensome interventions. Aim: A physician order form to withhold inappropriate life-sustaining interventions was initiated in 2009. The use of the form was facilitated by staff educational sessions and a palliative care consult service. This study aims to evaluate the impact of these interventions in 2010. Design: Retrospective medical chart review with comparisons was made for the following: baseline patient characteristics, orders concerning life-sustaining therapies, treatment provided in last 24 h of life, and discussion of specific life-sustaining therapies with patients and families. Settings/participants: This study included all adult patients who died in our hospital's general wards in 2007 ( N = 683) versus 2010 ( N = 714). Results: There was an increase in orders to withhold life-sustaining therapies, such as cardiopulmonary resuscitation (66.2%–80.0%). There was a decrease in burdensome interventions such as antibiotics (44.9%–24.9%) and a small increase in palliative treatments such as analgesia (29.1%–36.7%). There were more discussions on the role of cardiopulmonary resuscitation with conversant patients (4.6%–10.2%) and families (56.5%–79.8%) ( p -value all < 0.05). On multivariate analysis, the physician order form independently predicted orders to withhold cardiopulmonary resuscitation. Conclusions: A multifaceted intervention of a physician order form, educational sessions, and palliative care consult service led to an improvement in documentation of end-of-life discussions and was associated with an increase in such discussions and less burdensome treatments. There were small improvements in the proportion of palliative treatments administered.